2017
DOI: 10.1158/2159-8290.cd-16-0975
|View full text |Cite
|
Sign up to set email alerts
|

CREBBPInactivation Promotes the Development of HDAC3-Dependent Lymphomas

Abstract: Somatic mutations in CREBBP occur frequently in B-cell lymphoma. Here, we show that loss of CREBBP facilitates development of germinal center derived lymphomas in mice. In both human and murine lymphomas CREBBP loss of function resulted in focal depletion of enhancer H3K27 acetylation and aberrant transcriptional silencing of genes that regulate B-cell signaling and immune responses including class II MHC. Mechanistically, CREBBP regulated enhancers are counter-regulated by the BCL6 transcriptional repressor i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
276
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 242 publications
(301 citation statements)
references
References 42 publications
17
276
1
2
Order By: Relevance
“…While this paper was under review, 2 papers interrogating the role of Crebbp inactivation in murine B-cell lymphoma models were published. 34,49 Jiang et al reported downregulation of MHC class II genes with short hairpin RNA-mediated knock-down of Crebbp, but this was not reported by Zhang et al, using B-cell-specific deletion of Crebbp with cre recombinase, and only modest changes were shown in our study. The role of Crebbp loss compared with Crebbp KATdomain point mutation in the deregulation of MHC class II expression therefore requires further functional interrogation.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…While this paper was under review, 2 papers interrogating the role of Crebbp inactivation in murine B-cell lymphoma models were published. 34,49 Jiang et al reported downregulation of MHC class II genes with short hairpin RNA-mediated knock-down of Crebbp, but this was not reported by Zhang et al, using B-cell-specific deletion of Crebbp with cre recombinase, and only modest changes were shown in our study. The role of Crebbp loss compared with Crebbp KATdomain point mutation in the deregulation of MHC class II expression therefore requires further functional interrogation.…”
Section: Discussioncontrasting
confidence: 90%
“…GCB-cell development was significantly higher in all mice carrying the EmBcl2 transgene (P , .001) compared with strains without the transgene, and GCB-cell development was not significantly affected by Crebbp deletion in this background ( Figure 2). We observed only minor changes in the expression of MHC class II with Crebbp inactivation (supplemental Figure 5), similar to those observed with short hairpin RNA-mediated knock-down of Crebbp, 34 but far below the magnitude of those changes observed in primary FL with CREBBP mutation.…”
Section: Impaired B-cell Development Associated With Crebbp Losssupporting
confidence: 79%
“…To determine possible sources of NOTCH signaling in FLs and GC B-cells we measured expression of these genes in the principle FL and DLBCL cell lines used for this study (DoHH2, SC-1, OCI-Ly1 and SUD-HL-4), purified primary mature B-cell populations: NB, GC, CB, CC, MB (memory B), TPC (tonsillar plasma cell), BMPC (bone marrow plasma cell), and in a cohort of primary FL patients by RNA-seq (30,31). Expression of NOTCH ligands DLL1, DLL3, DLL4 and JAG1 was low in all of four cell lines, although JAG2 was expressed, and possibly relevant to NOTCH activation in vitro (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…70) or EP300 (3%-8%; ref. 71), both affecting a pathway that is also implicated in cancer (72). Several case reports indicate that individuals with RSTS are at increased risk of developing cancer, but the cancer risk is unknown and may be only moderately increased.…”
Section: Rubinstein-taybi Syndromementioning
confidence: 99%